Klûčevye imena vremeni v publicističeskom stile - Coneva, Liliâ (Stylistyka, 2021)
The paper diccusses key proper names in modem Russian - names of personalities that are at the focus of publikę attention. They, like key words in generał, have theer oron spe- cific features, e. g. high frequency and use in titles of joumalistic discourse. Special attention is paid on the use of key proper names in different language games conditioned by theirlinguistic and extralinguistic associative potential.